CHANGES IN CONTROL BELIEFS, EMOTIONAL STATUS AND PSYCHOSOCIAL ADAPTATION AMONG WOMEN WITH BREAST CANCER - Neipp, Mª del Carmen; López-Roig, Sofía; Terol, Mª Carmen; Pastor, Mª Angeles (Anales de Psicología / Annals of Psychology, 2009)
Studies using samples with chronic illnesses showed that con-trol beliefs are associated with better psychosocial adjustment and emo-tional status. Our aims were to describe changes and long-term influence of general control beliefs and specific control beliefs over psychosocial and emotional adjustment. Method: We analysed 131 breast cancer patients with unilateral primary breast cancer attending the standard follow-up protocol in the Oncology Unit at the General Hospital of Alicante, Spain. Different standard questionnaires were used included and we also de-signed specific questions for this study (control beliefs regarding follow-up protocol). Results: There were no significant changes in control beliefs nor on psychosocial and emotional adjustment. Patients had high general and specific control beliefs. Perceived Health Competence was the best predictor of emotional status. Finally, both general control beliefs and specific control beliefs predicted some psychosocial areas equally. Conclusions: Women had a good emotional status and psychosocial adaptation and had an external locus profile. Moreover, control beliefs maintain across time.